INDEPENDENŢA ENERGETICĂ A REPUBLICII MOLDOVA ŞI FACTORII CARE O CONDIŢIONEAZĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2009)
The energetic independence of any country is in direct connection with the existence of hydrocarbon reserves. In the Moldavian Republic there are two oil and gas fi elds of small dimensions but enough to show us that the hydrocarbons generation, migration and accumulation conditions are already demonstrated. Beside these, the existing oil and gas fi elds in exploitation on the Western side of the Prut river in Romania, as well as in the Eastern part of the Predobrogean Depression in Ukraine, proved that on the Moldavian territory of the above mentioned depression could be discovered some other oil and gas fi elds. The oil and gas fi elds discovery is conditioned by the modern geophysical and geochemical surveys execution.